PENINGKATAN HASIL BELAJAR DAN KEMAMPUAN MENGEKSPORASI PENGALAMAN SISWA MELALUI PEMBELAJARAN KONSTRUKTIVISTIK - Saputro, Hanri Eko (IAIN Padangsidimpuan, 2014)
Abstract: The result of the optimal learning of Islamic Religious Education would be a major capital for studentâs practice in the daily life. On the other hand the presentation of teaching religious education tends to be assessed indoctrinative and did not meaningful. So that, the result of learning is very low, especially on Shalat Jamak Qashar matter. The average mark isÂ only 72.06, the percentage of completeness is 34.71%, the students who are actively involved in learning is only 42.29%, and no students who expressed very interested in this way. This research try to explore the last students experiences by contructivistic learning. The result indicates that an increase in student learning outcomes, the average mark to be 85.28, the percentage of completeness to be 100%, and the students who are actively involved in learning to be 99%. Besides, the majority of students, in the interview, also stated that learning with contructivistic learning is very interesting.Keywords: Results of learning, the ability to explore, konstruktivistikÂ Abstrak: Hasil belajar pendidikan Agama Islam yang optimal akan menjadi modal utama untuk berlatih siswa dalam kehidupan sehari-hari. Di sisi lain presentasi mengajar pendidikan agama cenderung akan dinilai indoktrinasi dan tidak bermakna. Sehingga, hasil belajar sangat rendah, terutama pada Shalat Qashar JAMAK. Nilai Rata-rata hanya 72,06, persentase kelengkapan adalah 34,71%, siswa yang terlibat secara aktif dalam pembelajaran hanya 42,29%, dan tidak ada siswa yang menyatakan sangat tertarik dengan cara ini. Penelitian ini mencoba untuk mengeksplorasi siswa pengalaman terakhir dengan pembelajaran konstruktivis. Hasil penelitian menunjukkan bahwa peningkatan hasil belajar siswa, tanda-rata menjadi 85,28, persentase kelengkapan untuk menjadi 100%, dan siswa yang terlibat secara aktif dalam pembelajaran menjadi 99%. Selain itu, sebagian besar siswa, dalam wawancara, juga menyatakan bahwa pembelajaran dengan pembelajaran konstruktivis sangat menarik.Kata Kunci: Hasil belajar, kemampuan mengeksplorasi, konstruktivistik